2000
DOI: 10.1021/jp000130u
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ion Pairing in Lead Nitrate Solutions As Determined with 207Pb NMR Spectroscopy

Abstract: The temperature and concentration variations in 207Pb NMR shifts of Pb(NO3)2 in aqueous solutions are analyzed in terms of exchange between aquated lead ion and the Pb(NO3)+ ion complex according to the reaction PbNO3 +(aq) = Pb2+(aq) + NO3 -(aq). The analysis gives an enthalpy of dissociation of −3.0 ± 0.2 kcal mol-1 and an entropy of dissociation of −11.9 ± 0.4 cal K-1 mol-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The 207 Pb chemical shift is sensitive to the concentration of the sample [19,22] ; this has been attributed to the rapid interchange of cations and anions in solution. [22,23] Such measurements may prove effective in an educational setting (vide infra), so we investigated whether the effect can be replicated at a lower field strength by acquiring spectra of a series of samples of various concentrations at 1.4 T. Figure 4a illustrates a plot of the chemical shifts of Pb(NO 3 ) 2 as a function of the concentration of this sample dissolved in H 2 O. The observed trend is comparable with that reported by Harrison et al, [19] although at lower concentrations, our values suggest greater shielding, such that our predicted shielding at infinite dilution, −2,885 ppm, is significantly greater than that predicted by Harrison et al [19] In contrast, Dybowski et al [23] reported greater shielding values at lower concentrations than we observed.…”
Section: Solution Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 207 Pb chemical shift is sensitive to the concentration of the sample [19,22] ; this has been attributed to the rapid interchange of cations and anions in solution. [22,23] Such measurements may prove effective in an educational setting (vide infra), so we investigated whether the effect can be replicated at a lower field strength by acquiring spectra of a series of samples of various concentrations at 1.4 T. Figure 4a illustrates a plot of the chemical shifts of Pb(NO 3 ) 2 as a function of the concentration of this sample dissolved in H 2 O. The observed trend is comparable with that reported by Harrison et al, [19] although at lower concentrations, our values suggest greater shielding, such that our predicted shielding at infinite dilution, −2,885 ppm, is significantly greater than that predicted by Harrison et al [19] In contrast, Dybowski et al [23] reported greater shielding values at lower concentrations than we observed.…”
Section: Solution Samplesmentioning
confidence: 99%
“…[22,23] Such measurements may prove effective in an educational setting (vide infra), so we investigated whether the effect can be replicated at a lower field strength by acquiring spectra of a series of samples of various concentrations at 1.4 T. Figure 4a illustrates a plot of the chemical shifts of Pb(NO 3 ) 2 as a function of the concentration of this sample dissolved in H 2 O. The observed trend is comparable with that reported by Harrison et al, [19] although at lower concentrations, our values suggest greater shielding, such that our predicted shielding at infinite dilution, −2,885 ppm, is significantly greater than that predicted by Harrison et al [19] In contrast, Dybowski et al [23] reported greater shielding values at lower concentrations than we observed. Previously, Lutz and Stricker reported a 72-ppm difference between the chemical shifts for 1.0 M Pb(NO 3 ) 2 and that expected for the sample at infinite dilution [24] ; this compares with a range of 79 ppm observed here and 108 ppm reported by Harrison et al [19] Neue et al have discussed factors, such as the temperature and concentration dependence of 207 Pb chemical shifts, that explain many such discrepancies.…”
Section: Solution Samplesmentioning
confidence: 99%
“…For process involving ion solvation, one can investigate the NMR spectroscopy of the solvent such as water [18]. In addition, comparing experimental data to Fuoss theory leads to evaluate ion association phenomenon and the type of ionpair [1,8].…”
Section: Ion-pairing In Aqueous Solution Of Bafmentioning
confidence: 99%
“…The NMR method enables us to study the phenomenon of ion-pairing. When the exchange of the F À ion between the free state and ion-pair state (according to reaction 1) is fast, dependence of chemical shifts on the concentration of the F À ion can be treated as follows [18][19][20]38]:…”
Section: Ion-pairing In Aqueous Solution Of Bafmentioning
confidence: 99%
See 1 more Smart Citation